Peran Satuan Intelkam Polrestabes Bandung dalam Mencegah Kejahatan dan Pelanggaran Orang Asing di Wilayah Hukum Kota Bandung - Dea Ade Juliana; Lisdawati Wahjudin (Jurnal Sosial Politik Unla, 2019)
Factors influencing the prevention of crime and violations of foreigners include who is authorized to conduct surveillance, conduct surveillance everywhere, and what types of criminal acts and violations committed by foreigners. The obstacle in preventing foreigners is that the role of the intelligence unit is limited by the main tasks of the law, so that in fact these obstacles sometimes overlap with the Immigration with its main task. Efforts are made to overcome these obstacles by trying to re-establish good coordination with relevant agencies, especially with the Immigration sub-Wasdakim, to avoid overlapping in their respective main tasks. Based on the results of research and discussion it can be concluded that preventing crime and violations of strangers carried out by the intelligence unit's role, among others, by conducting investigations that must be fulfilled by conducting early detection (accompanying), monitoring (accompanying), socializing (ending) in order to obtain information obtained for immediate production of intelligence products in order to make plans Furthermore, with the relevant agencies, to conduct surveillance of foreigners, the Intelligence Unit must coordinate with the Immigration Service so that the existing data of the Intelligence Unit and the Immigration Service can be equalized, and there is no overlap in their main duties.